Estimation of SNR Including Quantization Error of Multi-Wavelength Lidar Receiver - Abed, Zena A.; Hummady, Muna M. (Al-Khwarizmi Engineering Journal, 2013)
This paper comprises the design and operation of mono-static backscatter lidar station based on a pulsed Nd: YAG laser that operates at multiple wavelengths. The three-color lidar laser transmitter is based on the collinear fundamental 1064 nm, second harmonic 532 nm and a third harmonic 355nm output of a Nd:YAG laser. The most important parameter of lidar especially daytime operations is the signal-to-noise ratio (SNR) which gives some instructions in designing of lidar and it is often limit the effective range. The reason is that noises or interferences always badly affect the measured results. The inversion algorithms have been developed for the study of atmospheric aerosols. Signal-to-noise ratio (SNR) of three-color channel receivers were presented while averaging together 1, 20, 50 and 100 lidar returns and combined to the signal to noise ratio associated with the quantization process for each channel.